Journal of School-Makers - Nancy Vansieleghem; Mattijs Driesen (Revista Portuguesa de Pedagogia, 2022)
In this contribution we consider the educational potential of the camera as a collective study practice against the background of today’s proliferation of audio-visual media in education. Distinct from scholarship that investigates how the camera can be integrated in education to activate the student in terms of learning, and in terms of socialization or qualification, this contribution re-assesses the educational significance of cinematographic media through a radical affirmation of its potential to make school. To do so, we rely upon the TV-film Diario di un Maestro (Diary of a Schoolmaster) by the Italian filmmaker Vittorio De Seta (1971), and link it with the camera practice of the French filmmaker and pedagogue Fernand Deligny, who uses the camera as a practice that instead of working for, works within the (life) world. These concrete camera practices enable us, not only to reconsider what making school could mean, but also how the camera and its potentiality to make fiction can make school real.